Den etnologiska kicken - Lundgren, Anna Sofia; Nilsson, Bo (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2011)
Much ethnography is experimental in one way or another, fieldwork practices as well as the written representations. In this text, we use commentaries on thesis drafts as examples in order to track and highlight how supervising and textreadings may be performative in the pursuit of what we would call a kick-seeking ethnography.